2006
DOI: 10.1086/507532
|View full text |Cite|
|
Sign up to set email alerts
|

HIV/AIDS: Antiretroviral Therapy for Hepatitis B Virus–HIV–Coinfected Patients: Promises and Pitfalls

Abstract: Coinfections with human immunodeficiency virus (HIV) and hepatitis B virus (HBV) are common globally. HIV infection modifies the course of HBV infection by increasing rates of chronicity, prolonging HBV viremia, and increasing liver-related morbidity. To minimize the emergence of HIV and/or HBV resistance, as well as the emergence of liver enzyme flares, the treatment of both infections should be coordinated. Lamivudine or emtricitabine monotherapy readily selects resistant strains in the YMDD motif of the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…Some researchers focus on treating one virus at a time, while others declare it safe to treat both simultaneously. If treatment is indicated in an HBV/HIV co-infected patient, some factors such as combination ART for HIV infection, the severity of liver disease, probability of various reactions and potential adverse events should be taken into account 42 . When treatment is necessary for both HBV and HIV infections, HAART is needed for HIV.…”
Section: Treating Hiv and Hbv Infections Concomitantlymentioning
confidence: 99%
“…Some researchers focus on treating one virus at a time, while others declare it safe to treat both simultaneously. If treatment is indicated in an HBV/HIV co-infected patient, some factors such as combination ART for HIV infection, the severity of liver disease, probability of various reactions and potential adverse events should be taken into account 42 . When treatment is necessary for both HBV and HIV infections, HAART is needed for HIV.…”
Section: Treating Hiv and Hbv Infections Concomitantlymentioning
confidence: 99%
“…It is estimated that there are over 500 million cases of malarial infection annually, mostly in Africa, and dual infection of HIV and malaria facilitates the geographical expansion of each [64]. HCV and HBV infections are also highly prevalent among the HIV population [65,66].…”
Section: Hiv Diversity Enables Escape From Detectionmentioning
confidence: 99%
“…These coinfections are not only widespread and increase mortality rates, but they also reduce the accuracy of HIV tests [62,[65][66][67][68][69], creating a need for diagnostics that can quickly and reliably account for these coinfections. Using TB as an example, the analytical and clinical techniques used for diagnosis include sputum smear microscopy and culture, but these methods are inaccurate (microscopy misses 50% of cases) and not rapid (cultures may require days) [62,70].…”
Section: Presence Of Coinfectionsmentioning
confidence: 99%
“…An additional double-blind, placebo-controlled trial showed that tenofovir may be a useful component of antiretroviral therapy for HIV/HBV co-infected patients. Importantly, tenofovir is equivalent to adefovir in its ability to reduce HBV DNA levels, and may, in fact, be superior [17] . If HBV treatment can be deferred until combination antiretroviral therapy for HIV infection is needed, the combination of tenofovir plus lamivudine or emtricitabine will be the potent HBV therapy and a solid backbone for HIV combination antiretroviral therapy, and a potent treatment for HBV and it likely decreases the emergence of HBV resistance.…”
Section: Tenofovir (Viread Pmpa)mentioning
confidence: 99%